Association of IL – 23 R rs 7518660 Gene Polymorphism with Susceptibility and Disease Severity of Pulmonary Tuberculosis - Widowati, Yenny; Sugiri, Yani Jane; Putu, Ngakan; Setijowati, Nanik (Indonesian Journal of Tropical and Infectious Disease, 2022)
Pulmonary Tuberculosis (TB) is a global health problem. Of all people infected with Mycobacterium tuberculosis only a small proportion develops into TB. IL 23 is the key cytokine in the pathogenesis of TB infection. This study aims to determine the association of IL-23 R rs 7518660 gene polymorphism with susceptibility and disease severity of Pulmonary TB. A case control study involved 105 people consisting of 31 drug sensitive pulmonary TB patients, 40 patients with drug-resistant pulmonary TB and 34 healthy subjects as a control. IL-23 R rs 7518660 gene polymorphism G allele increases susceptibility to both TB drug-sensitive and drug-resistant. G and A allele, AA and AG genotypes indicates (p value >0.05) in correlation with disease severity based on lesion in chest x-ray and high load of Mycobacterium tuberculosis in sputum. There was a significant relationship between allele A and susceptibility to pulmonary TB with an odds ratio of 0.231. It showed that patients with A alleles (AG and AA genotypes) were at risk of developing TB by 1/0.231 = 4.33 times lower than patients with GG genotypes. Meanwhile, the relationship of the G allele with susceptibility to pulmonary TB obtained (p value <0.05) and an odds ratio value of 0.127 indicating that patients with G alleles (GG and AG genotypes) were at risk of developing TB of 1/0.127 = 7.87 times higher than in patients with the AA genotype. Conclusion: We found significant correlation between IL-23 R rs 7518660 gene polymorphism G allele with susceptibility to pulmonary TB, but the result was not significant with disease severity.